2005
DOI: 10.1007/bf03015769
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of chronic pain in Québec: a study of hospital-based services offered within anesthesia departments

Abstract: P Pu ur rp po os se e: : Little or no information exists on the services that are currently available for the treatment of chronic pain across the different regions of Canada. As a first step, this study documented the hospital-based resources and services offered for the management of chronic non-cancer pain within anesthesia departments in Québec. M Me et th ho od ds s: :In collaboration with the Association of Anesthesiologists of Québec and the Société québécoise de la douleur, a provincial survey was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
(22 reference statements)
1
23
0
3
Order By: Relevance
“…Multidisciplinary pain treatment is recognized as the optimal paradigm 3,B for a good proportion of these patients, but access is restricted due to the limited number of facilities and long waiting lists. 4,5 A recent Canadian survey identified six months as the median wait time for a first appointment in public multidisciplinary pain treatment facilities (MPTFs). This means that 50% of patients have to wait six months or more (with a range of up to five years) for access to appropriate pain treatment, with 30% of clinics reporting waitlists of more than one year and vast areas of the country remaining unserviced.…”
Section: Résumémentioning
confidence: 99%
“…Multidisciplinary pain treatment is recognized as the optimal paradigm 3,B for a good proportion of these patients, but access is restricted due to the limited number of facilities and long waiting lists. 4,5 A recent Canadian survey identified six months as the median wait time for a first appointment in public multidisciplinary pain treatment facilities (MPTFs). This means that 50% of patients have to wait six months or more (with a range of up to five years) for access to appropriate pain treatment, with 30% of clinics reporting waitlists of more than one year and vast areas of the country remaining unserviced.…”
Section: Résumémentioning
confidence: 99%
“…A recent survey of hospital-based services for non-cancer pain treatment in Quebec found that almost 30% of anesthesiologists in that province were involved in treating chronic pain. 2 Approximately one Canadian in five suffers from chronic non-malignant pain, defined as pain present on most days, for a minimum of six months. The prevalence increases with age.…”
mentioning
confidence: 99%
“…Veillette et al 2 studied pain clinic services within hospital-based anesthesia departments in Quebec and found that the province was underserved, both in terms of limited access and inadequate quality of services offered. In the latter six months of 2002, 4,500 patients were waiting for their first appointment in a pain clinic.…”
mentioning
confidence: 99%
See 2 more Smart Citations